ANALISIS PUTUSAN PN MATARAM No. 8/Pdt.G.S/2024 TENTANG EKSEKUSI JAMINAN FIDUSIA DAN ISU LOSS OF USE PASKA PUTUSAN MAHKAMAH KONSTITUSI: Analysis f The Mataram PN Decision No.8/Pdt.G.S/2024 On The Execution Of Fiduciary Guarantees And The Issue Of Loss Of Use After The Constitutional Court Decision - Muhammad Chairul Azizy (PESOLAH: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study examines Decision No. 8/Pdt.G.S/2024 of the Mataram District Court concerning the execution of fiduciary security following Constitutional Court Decision No. 18/PUU-XVII/2019. It focuses on the prohibition of unilateral execution by creditors and the legal reasoning behind the rejection of the debtor’s claims for material, immaterial, and loss-of-use damages. Using a normative juridical methodology, the study finds that the judges consistently applied the Constitutional Court’s interpretation, declaring the unilateral repossession of the vehicle without a court order as an unlawful act. However, the rejection of all compensation claims reflects insufficient protection for the debtor’s actual losses, particularly loss of use. The decision also highlights a normative gap regarding proof of non-economic damages in fiduciary execution cases. Therefore, more operational judicial guidelines are needed to ensure that civil judgments provide not only formal justice but also substantive justice for debtors.